How can states ensure access to personal assistance when service delivery is decentralized? : A multi-level analysis of Iceland, Norway and Sweden - Brennan, Ciara; Rice, James Gordon; Traustadóttir, Rannveig; Anderberg, Peter (Scandinavian Journal of Disability Research, 2017)
Article 19 of the United Nations (UN) Convention on the Rights of Persons with Disabilities requires states to ensure that persons with disabilities have access to a range of support services, including personal assistance. The Convention is an agreement between state parties and the UN. However, in practice, disability services are often implemented at the local level. Drawing on the findings of qualitative research in Iceland, Norway and Sweden, this paper examines a paradox whereby states commit to ensure access to support services, but decentralize responsibility to autonomous and independent local governments. A multi-level governance framework is applied to analyse the findings of qualitative inquiry with policy-makers, local government officials and leaders of independent living organizations in all three Nordic countries. A multi-level analysis highlights the tensions and contradictions between decentralization and human rights commitments. © 2016 Nordic Network on Disability Research